Possibilities of Detecting Pre-clinical Forms of Atherosclerosis During Periodic Preventive Inspections in Organized Collectives at Workers of Machine Building Enterprises - A. N. Britov; N. A. Eliseeva; A. D. Deev; S. A. Shalnova (Рациональная фармакотерапия в кардиологии)
Aim. To study the structural and functional features of the carotid and femoral arteries using ultrasound duplex scanning of them in patients with hypertension undergoing periodic preventive medical examination.Material and methods. Periodic preventive examination was carried out for 2431 employees (1311 men and 1120 women) aged 20-65 years using a specially developed questionnaire, blood pressure measurement, anthropometry, total cholesterol test. Hypertensive men were assessed for preclinical manifestations of atherosclerosis by ultrasound duplex scanning of the carotid and femoral arteries.Results. Hypertensive men (BP ≥140/90 mmHg and/or taking antihypertensive drugs; n=176, mean age 43.5 years) were included in the study. An increase in the thickness of the intima-media complex in the carotid arteries was found in 22.2% (n=38) people, in the femoral arteries – in 34.1% (n=60) people, in both basins – in 16.5% (n= 29) man. Atherosclerotic plaques in the carotid arteries were found in 40.3% of people (n=71), and in the femoral arteries – in 34.7% (n=61) of people, in both pools – in 23.9% (n=42) of men.Conclusion. Ultrasound diagnostic using modern ultrasound scanners is a highly informative method for non-invasive diagnosis of atherosclerosis in the arteries of the carotid and femoral basins in employees of a large industrial enterprise with arterial hypertension in the conditions of the medical and sanitary department. Carrying out these diagnostic approaches is advisable when organizing periodic medical examinations in order to improve primary prevention, as well as to prevent the aggravation of the identified pathological process, reduce complications, improve quality and increase life expectancy.